From Observation to Co-Creation: A Netnographic Review of AI-Driven Consumer Behavior - Ahmad Mundzir; Kuniarti Pratiwi (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
As artificial intelligence (AI) continues to transform the landscape of digital consumer experiences, traditional netnographic methods face significant disruption—both in terms of methodological execution and theoretical framing. This systematic review explores how the growing presence of AI, functioning not only as a technological tool but also as an agentic participant, reshapes the way netnography is practiced in marketing and consumer behavior research. Recognizing a widening gap in the literature, the study aims to synthesize current conceptual and methodological advancements at the intersection of ethnographic inquiry and intelligent systems. Employing the PRISMA 2020 protocol for systematic reviews, 43 peer-reviewed journal articles published between 2013 and 2024 were retrieved from Scopus and Web of Science databases. A thematic synthesis of these articles reveals five dominant themes: the methodological evolution of netnography within online consumer communities; the role of AI in predictive personalization; emerging patterns of consumer–AI value co-creation; new relational models of human–AI interaction; and ethical and epistemological challenges posed by AI-augmented ethnography. These themes collectively inform the development of a novel conceptual framework, AI-Netnography which positions both human and algorithmic agents as co-constructors of meaning, identity, and experience. By reimagining netnographic inquiry for AI-mediated environments, this review not only advances the field of qualitative marketing research but also proposes new pathways for ethically responsible and epistemologically inclusive digital consumer studies.